Pengaruh Dukungan Sosial Keluarga dan Kreativitas terhadap Minat Berwirausaha Mahasiswa - Tri Kartika Putri; Ahyanuardi Ahyanuardi (Jurnal Pendidikan Teknik Elektro, 2021)
This study aims to determine the Effect of Family Social Support and Creativity on Entrepreneurial Interest in Electrical Engineering Education Study Program Students During the Covid-19 Pandemic. This research method uses a quantitative approach, meaning that all information or data is realized in numbers and the analysis is based on statistical analysis. The type of research used is causal associative research. The research instrument uses a questionnaire that has been validated by entrepreneurship lecturers and is tested before the questionnaire is distributed to students of Electrical Engineering Education, after testing the questionnaire is tested for validity and reliability. Assessment of research instruments using a Likert scale. Data analysis in this study used multiple linear regression to test the hypothesis using the T-test (t-test) and F test. The T-test was used to determine the partial effect of the independent variable on the dependent variable. The F test is used to determine the simultaneous effect of the independent variable on the dependent variable. The results showed that (1) family social support had no effect on interest in entrepreneurship (2) creativity had a positive and significant influence on interest in entrepreneurship (3) family social support and creativity had a positive and significant influence on interest in entrepreneurship.